2016
DOI: 10.1002/1873-3468.12479
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of CYP260A1 from Sorangium cellulosum to investigate the 1α‐hydroxylation of a mineralocorticoid

Abstract: In this study, we report the crystal structure of the cytochrome P450 CYP260A1 (PDB 5LIV) from the myxobacterium Sorangium cellulosum So ce56. In addition, we investigated the hydroxylation of 11-deoxycorticosterone by CYP260A1 by reconstituting the enzyme with the surrogate redox partners adrenodoxin and adrenodoxin reductase. The major product of this steroid conversion was identified as 1a-hydroxy-11-deoxycorticosterone, a novel D4 C-21 steroidal derivative. Furthermore, we docked the substrate into the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Another product—P3—had a mass of m / z [ M +H] + 361.2007; the calculated mass of molecular formula C 21 H 29 O 5 + was 361.2010. This might be the result of the presence of either a double bond or a keto group or of epoxide formation because both keto groups and epoxides can form from hydroxy groups . It is possible that P3 might be a product of oxidation of P2 at C21 (C−OH→C=O) to give a ketoacid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another product—P3—had a mass of m / z [ M +H] + 361.2007; the calculated mass of molecular formula C 21 H 29 O 5 + was 361.2010. This might be the result of the presence of either a double bond or a keto group or of epoxide formation because both keto groups and epoxides can form from hydroxy groups . It is possible that P3 might be a product of oxidation of P2 at C21 (C−OH→C=O) to give a ketoacid.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CYP514C3 from Streptomyces griseus and CYP154C5 from Nocardia francinica can oxidize steroids such as progesterone, testosterone, nandrolone, dehydroepiandrostenedione, and androstenedione at the 16α position . Recently, it has been shown that CYP260A1 and CYP260B1 from Sporangium cellulosum and CYP109E1 from B. megaterium DSM319 can also hydroxylate steroids …”
Section: Introductionmentioning
confidence: 99%
“…Both the peroxygenases catalyze hydroxylation at the C21 position of cortisone, prednisone, and 11-deoxycortisol substrates and subsequently convert them into possible carboxylic acid that finally leads to C-C bond cleavage forming 17-ketosteroids [14]. It is believed that the possibility of formation of oxidation products could be due to the presence of a double bond or formation of a keto or epoxide, as keto groups and epoxides can form from hydroxyl groups [36,37]. However, in contrast to the pattern of reaction products formation by peroxygenase, with the increase in the time of the reaction catalyzed by CYP154C8, no change in C-C bond cleavage product formation was observed, although sequential hydroxylation of such products (17-ketosteroids) was observed in traces, while increase in the formation of di-hydroxylated product from 21-hydroxyprednisone was observed with the increase in reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…S7). It is believed that the possibility of formation of oxidation products could be due to the presence of a double bond or formation of a keto or epoxide, as keto groups and epoxides can form from hydroxyl groups [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…CYP154C family P450s show 16␣-hydroxylation activities toward various steroidal substrates (13)(14)(15). CYP260A1 of the CYP260A family of P450s is able to convert various C 19 steroids at the 1␣ position, while CYP260B1 has been identified as a 6␤-and 9␣-hydroxylase of C 21 steroids (16,17). On the other hand, although many fungal P450s are referred to as being involved in steroid hydroxylations, not many of them have been biochemically characterized.…”
mentioning
confidence: 99%